Air quality study at critical area in Perlis - Siti Dzulaiha Binti Abidin (School of Environmental Engineering Universiti Malaysia Perlis, 2011)
Air pollution is a serius environmental problem and may bring health impact to human. This paper will focus on the particulate matter with a diameter lass than 10pm (PM10). this paper are carried out to determine the concentration of particulate matter (PM10) at the atmosphere, to determine the source of pollutant that contribute to the fluctuation of Pm10 concentration and to study the effects of PM10 to human health, environment, economy and also social life. using E-sampler, airborne particulate matter has been collected and analysed. This project was carried out at Chuping , Perlis. Meteorological Chuping department were selected as a monitoring station and five kilometre radius from station are selected as a surveying area for determine source and the effects of the pollutant.